ANEKSJA KOLEKTYWU CZY DYKTAT WYBIÓRCY? Z ZAGADNIEŃ ANTOLOGII TŁUMACZEŃ (NA PRZYKŁADZIE NOWYCH WYBORÓW POEZJI ROSYJSKIEJ) - Goczał, Ewa Maria (Przegląd Rusycystyczny, 2017)
The article attempts to present the comparison of two translator’s achievements: Zbigniew Dmitroca’s Radio Swoboda and Jerzy Czech’s Wdrapałem się na piedestał. The anthologist’s work is considered here as both the act of translation and revelation — joining the translation of literary texts and their compilation in anthologies with scrutinizing the particular writers and literary phenomena as well as the process of translation itself, and introducing a new, transforming quality to the native poetry. A translator-anthologist can be perceived in that perspective as a link between two literary cultures, and also as an initiator of changes and an independent creator who develops, in his own language and on his own conditions, a certain new Polish canon of Russian poetry.